A simulated coating for frozen-thawed soil and a preparation method thereof

By preparing frozen-thaw soil simulation coatings, the mineral and organic matter components of the soil particles are simulated by using crosslinking agents, photoinitiators, soluble minerals and organic matter components on the surface of soil particles, the problem of insufficient simulation of soil environmental simulation in the existing technology is solved, and high simulation simulation of soil pore channels is achieved, helping to study the impact of soil pollutant migration.

CN119752232APending Publication Date: 2025-04-04中国地质环境监测院(自然资源部地质灾害技术指导中心)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510005419.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art is difficult to highly simulate the surface structural characteristics of soil particles, especially in the process of simulating pollutants migration and changes in soil, which affects the degree of simulation and accuracy of the soil environment.

Method used

By preparing a simulated coating for frozen and thawing soil, the mineral and organic matter components are simulated on the surface of soil particles by using crosslinking agents, photoinitiators, soluble minerals and organic matter components to achieve high simulation of the surface of soil pore channels.

Benefits of technology

It significantly improves the degree of simulation of the soil environment, can truly reduce the objective conditions on the surface of soil particles, and helps to study the transmission mechanism of moisture, gas and nutrients in soil pore channels, especially the impact of soil pollutant migration under freeze-thaw conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a simulated coating of frozen-thawed soil and a preparation method thereof. The simulated coating of the frozen-thawed soil includes components such as a cross-linking agent, a photoinitiator, and soluble minerals, which are used to simulate the coating surface of natural soil, and to achieve simulation of components such as mineral components and organic matter in the soil. The preparation method of the simulated coating of the frozen-thawed soil comprises the following steps: under 20-25°C, sequentially adding components such as a cross-linking agent, a photoinitiator, and soluble minerals, mixing evenly by low-speed stirring, obtaining an aqueous solution containing soluble minerals, and then degassing and filtering to obtain the simulated coating of the frozen-thawed soil. The preparation method of the simulated coating of the frozen-thawed soil is simple and efficient, and the simulated coating of the formed frozen-thawed soil can accurately restore the real environment of the soil, improve the simulation degree of the soil environment in the prior art, and produce excellent effects and effects on the study of the migration and change of soil pollutants and soil environmental governance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of soil simulation, and in particular to a simulated coating of freeze-thaw soil and a preparation method thereof. Background Art

[0002] Soil is a complex ecological environment, which is not only reflected in the soil pore structure, but also in the composition of the soil porous medium layer. The components of the soil porous medium layer include soil minerals, organic matter and microorganisms, etc. These components together constitute the porous medium characteristics of the soil. Studying these components of the soil porous medium layer is crucial to understanding the structure of the soil environment. In the simulation research of soil environment, most studies focus on the simulation of soil pore distribution structure, while there are relatively few studies on the high-simulation simulation of the surface of the soil medium layer. The migration and change of pollutants in the soil are not only affected by the porous medium structure of the soil, but also by the characteristics of the porous medium of the soil. Therefore, in order to better simulate the soil environmental structure, deeply understand the interaction between soil particles and the environment, and the influence of soil particles on the migration of pollutants, it is urgent to provide a soil simulant that can highly simulate the surface structural characteristics of soil particles. Summary of the invention

[0003] In order to overcome the difficulties of the above-mentioned prior art, the present technical solution provides a simulated coating of frozen-thawed soil which is simple to prepare, has good simulation performance, and can highly restore the characteristics of soil components.

[0004] The specific technical solutions include the following:

[0005] A simulated coating for frozen-thawed soil, wherein the coating comprises the following components by weight percentage:

[0006] Crosslinking agent 0.5%-5%;

[0007] Photoinitiator 0.01%-0.1%;

[0008] Soluble minerals 10%-75%;

[0009] The rest is deionized water, and the sum of each component is 100%.

[0010] Among them, soluble minerals include montmorillonite and hydromica.

[0011] Further, the soluble minerals are composed of 50% montmorillonite and 50% hydromica by weight. Further, the soluble minerals are composed of 20% montmorillonite, 12% vermiculite and 5% hydromica by weight.

[0012] Furthermore, the soluble mineral components by weight percentage are 30%-50% hydromica, 10% vermiculite, 5% kaolinite and 3% montmorillonite.

[0013] Furthermore, the crosslinking agent is ethylene glycol dimethacrylate, and the photoinitiator is benzophenone. Furthermore, the coating is further added with 0.1%-2% thickener by weight, and the thickener is carboxymethyl cellulose.

[0014] Furthermore, the simulated coating is also added with 3.3%-6.3% organic matter by weight, wherein the organic matter is humic acid.

[0015] The method for preparing the simulated coating of freeze-thaw soil comprises the following steps:

[0016] a) adding the crosslinking agent into deionized water at a ratio of 0.5% to 5% at 20-25°C and stirring at a low speed until it is completely dissolved;

[0017] b) adding 0.01%-0.1% photoinitiator to the mixed solution and stirring at a low speed for 15-20 minutes to fully dissolve the photoinitiator;

[0018] c) slowly adding the soluble mineral into the mixed solution obtained in step b), stirring at a low speed for 25-35 minutes to uniformly suspend the mineral particles in the solution, and obtaining an aqueous solution containing the soluble mineral;

[0019] d) Degas the aqueous solution containing soluble minerals and control the vacuum degree at -0.08MPa~-

[0020] 0.1MPa, degassing time is 15-30 minutes;

[0021] e) filtering the treated solution to remove particulate impurities larger than 5 μm, and storing the filtered solution in a light-proof container to prevent the photoinitiator from reacting prematurely.

[0022] Furthermore, in steps a), b) and c), the mixed solution is stirred at a speed of 150-

[0023] 500rpm.

[0024] Furthermore, 0.1%-2% thickener is added to the soluble mineral aqueous solution obtained in step c).

[0025] This technical solution uses a cross-linking agent, a photoinitiator, soluble minerals and organic matter to prepare a simulated coating layer of soil, thereby achieving simulation of mineral components and organic matter in the soil, truly restoring the objective conditions of the pore channel surface in natural soil, and providing a more accurate simulation platform for simulating specific soil environments in the laboratory, thereby improving the degree of simulation of soil environments in the prior art; at the same time, the application of the freeze-thaw soil simulation coating is more conducive to studying the transmission mechanism of water, gas and nutrients in soil pore channels, especially for the study of the migration behavior of soil pollutants under freeze-thaw conditions. By setting up a simulated coating, the influence of the soil particle surface on the migration of pollutants under temperature changes can be highly restored, which has an excellent effect on studying the migration changes of soil pollutants and soil environmental governance. Therefore, the simulated coating of freeze-thaw soil protected by this technical solution has important value and significance in studying soil agricultural production, soil environmental governance and other aspects. DETAILED DESCRIPTION

[0026] The simulated coating of frozen-thawed soil and its preparation method described in this technical solution mainly use the soil in my country's seasonal frozen soil areas as the main simulation research object, providing an experimental simulation basis for further exploring the changes in the internal environment of the soil during the freezing and thawing process. The simulated coating and its preparation method protected by this technical solution can be applied to the simulation of various types of soil, not limited to the seasonal frozen soil areas described herein.

[0027] The simulated coating comprises 0.5-5% crosslinking agent, 0.01%-0.1% photoinitiator, 10%-75% soluble minerals, and the rest is deionized water, and the sum of all components is 100%, wherein the soluble minerals include montmorillonite and hydromica.

[0028] Embodiment 1: Take the black soil in Lishu County, Changchun City, Jilin Province as an example. After collecting black soil samples and determining them in the laboratory, the mineral components of the black soil in the region account for about 35-70% by weight of the soil, and the mineral components are mainly montmorillonite and hydromica, montmorillonite accounts for about 26% of the total mass of the mineral, and hydromica accounts for about 25% of the total mass of the mineral. According to the experimental needs, montmorillonite and hydromica are mixed in a mass ratio of 1:1 to form a soluble mineral simulating black soil, and the simulated coating of the black soil is composed of 0.5-5% cross-linking agent, 0.01%-0.1% photoinitiator, 35%-70% of a mixture of montmorillonite and hydromica in a mass ratio of 1:1 and deionized water by weight percentage. In particular, the black soil simulated coating includes 3% cross-linking agent, 0.05% photoinitiator, 65% montmorillonite and hydromica mixture (mass ratio 1:1) and deionized water, and the sum of each component is 100%.

[0029] Example 2: Taking the chernozem in Gongzhuling County, Changchun City, Jilin Province as an example. After collecting samples and measuring them in the laboratory, it is found that the mineral content in the area is about 10-30% by weight of the soil, and the mineral components are mainly montmorillonite, vermiculite and hydromica. Based on the total mass of chernozem minerals, montmorillonite accounts for 20%, vermiculite accounts for 12%, and hydromica accounts for 5%. In the simulation, montmorillonite, vermiculite and hydromica are selected and mixed in a mass ratio of 4:2:1 to prepare soluble minerals for simulating chernozem. The components of the simulated coating of chernozem include, by weight percentage, 0.5-5% of a crosslinking agent, 0.01%-0.1% of a photoinitiator, 10%-30% of a soluble mineral mixed with montmorillonite, vermiculite and hydromica in a mass ratio of 4:2:1, and deionized water. In particular, the simulated coating of chernozem includes 0.5% of a crosslinking agent, 0.01% of a photoinitiator, 15% of a mixture of montmorillonite, vermiculite and hydromica (mass ratio 4:2:1) and deionized water, and the total of the components is 100%.

[0030] Example 3: Take the dark brown soil in Shuangyang District, Changchun City, Jilin Province as an example. After collecting samples and laboratory determination, the mineral content in the area is about 20-35% by weight of the soil, and the mineral components are mainly hydromica, vermiculite, kaolinite and montmorillonite. Based on the total mass of the collected dark brown soil minerals, hydromica accounts for 50%, vermiculite accounts for 10%, kaolinite accounts for 5%, and montmorillonite accounts for 3%. In the experiment, hydromica, vermiculite, kaolinite and montmorillonite were selected and mixed in a mass ratio of 20:4:2:1 to prepare soluble minerals for simulating dark brown soil. The simulated coating of dark brown soil is composed of 0.5-5% cross-linking agent, 0.01%-0.1% photoinitiator, 20%-35% mixture of hydromica, vermiculite, kaolinite and montmorillonite (mass ratio is 20:4:2:1) and deionized water by weight percentage. In particular, the simulated coating of dark brown soil is composed of 2% cross-linking agent, 0.05% photoinitiator, 30% mixture of hydromica, vermiculite, kaolinite and montmorillonite (mass ratio is 20:4:2:1) and deionized water, and the sum of all components is 100%.

[0031] The cross-linking agent described in the technical solution is preferably ethylene glycol dimethacrylate, and the photoinitiator is preferably benzophenone.

[0032] The simulated coating described in the technical solution is further added with 0.1%-2% thickener by weight, wherein the thickener is preferably carboxymethyl cellulose.

[0033] Example 4, taking the dark brown soil in Shuangyang District, Changchun City, Jilin Province as an example. After collecting dark brown soil samples and measuring them in the laboratory, the mineral components of the dark brown soil in the area accounted for about 20-35% by weight of the soil, and the mineral components were mainly hydromica, vermiculite, kaolinite and montmorillonite. Based on the total mass of the collected dark brown soil minerals, hydromica accounted for 50%, vermiculite accounted for 10%, kaolinite accounted for 5%, and montmorillonite accounted for 3%. In the experiment, hydromica, vermiculite, kaolinite and montmorillonite were selected and mixed in a mass ratio of 20:4:2:1 to prepare soluble minerals simulating dark brown soil. The simulated coating of the dark brown soil consists of 0.5-5% cross-linking agent, 0.01%-

[0034] The invention relates to a method for preparing a dark brown soil simulation coating comprising: 0.1% photoinitiator, 20%-35% mixture of hydromica, vermiculite, kaolinite and montmorillonite, 1.2% thickener and deionized water. In particular, the dark brown soil simulation coating comprises 4% ethylene glycol dimethacrylate, 0.08% benzophenone, 30% mixture of hydromica, vermiculite, kaolinite and montmorillonite (mass ratio 20:4:2:1), 1.2% carboxymethyl cellulose and deionized water, and the total amount of each component is 100%.

[0035] Example 5: Taking the chernozem in Gongzhuling County, Changchun City, Jilin Province as an example. After collecting samples and measuring them in the laboratory, it was found that the mineral content of the chernozem in the area was about 10-30% by weight of the soil, and the mineral components were mainly montmorillonite, vermiculite and hydromica. Based on the total mass of chernozem minerals, montmorillonite accounted for 20%, vermiculite accounted for 12%, and hydromica accounted for 5%. In the simulation, montmorillonite, vermiculite and hydromica were selected and mixed in a mass ratio of 4:2:1 to prepare soluble minerals for simulating chernozem. The components of the simulated coating of chernozem include 0.5-5% of a crosslinking agent, 0.01%-0.1% of a photoinitiator, 10%-30% of a soluble mineral mixed with montmorillonite, vermiculite and hydromica, 0.1% of a thickener and deionized water, and the total percentage of each component is 100%. In particular, the simulated coating of chernozem includes 1.2% of ethylene glycol dimethacrylate, 0.02% of benzophenone, 15% of a mixture of montmorillonite, vermiculite and hydromica (mass ratio 4:2:1), 0.1% of carboxymethyl cellulose and deionized water, and the total percentage of each component is 100%.

[0036] Example 6: Take the black soil in Lishu County, Changchun City, Jilin Province as an example. After collecting black soil samples and measuring them in the laboratory, the mineral components of the black soil in the area account for about 35-70% by weight of the soil, and the mineral components are mainly montmorillonite and hydromica, montmorillonite is about 26% of the total mass of the mineral, and hydromica is about 25% of the total mass of the mineral. According to the experimental needs, montmorillonite and hydromica are mixed in a mass ratio of 1:1 to form a soluble mineral simulating black soil. The simulated coating of the black soil is composed of 0.5-5% cross-linking agent, 0.01%-0.1% photoinitiator, 35%-70% soluble mineral, 2% thickener and deionized water by weight percentage. In particular, the simulated coating of the black soil includes 3% ethylene glycol dimethacrylate, 0.05% benzophenone, 65% montmorillonite and hydromica mixture (mass ratio 1:1), 2% carboxymethyl cellulose and deionized water, and the sum of each component is 100%.

[0037] The simulated coating described in the technical solution also contains 3.3%-6.3% organic matter by weight, wherein the organic matter is humic acid.

[0038] Example 7: Take the simulated chernozem in Gongzhuling County, Changchun City, Jilin Province as an example. Specifically, according to the collected chernozem samples, the average organic matter content value of the surface soil depth of 0cm-18cm is selected. After measurement, the organic matter content of the chernozem is about 3.3% of the total mass of the chernozem. In particular, based on the weight percentage of the simulated coating, 3.3% humic acid (purchased from Shanghai Yuanye Biotechnology Co., Ltd.) is selected as the organic matter component. In particular, the black soil simulation coating includes 1.2% ethylene glycol dimethacrylate, 0.02% benzophenone, 15% montmorillonite, vermiculite and hydromica mixture (mass ratio 4:2:1), 0.1% carboxymethyl cellulose, 3.3% humic acid and deionized water, and the sum of each component is 100%.

[0039] Example 8: Take the simulation of black soil in Lishu County, Changchun City, Jilin Province as an example. Specifically, according to the collected black soil organic matter content, the average organic matter content value of the soil depth 0cm-20cm is selected. After measurement, the black soil organic matter content accounts for 6.3% of the black soil mass percentage. In particular, based on the weight percentage of the simulated coating, 6.3% humic acid (purchased from Shanghai Yuanye Biotechnology Co., Ltd.) is selected as the organic matter component. The black soil simulation coating includes 3% ethylene glycol dimethacrylate, 0.05% benzophenone, 65% montmorillonite and hydromica mixture (mass ratio 1:1), 2% carboxymethyl cellulose and 6.3% humic acid and deionized water, and the sum of each component is 100%.

[0040] Similarly, a simulated coating was prepared for dark brown soil in Shuangyang District, Changchun City, Jilin Province. In the simulation experiment, the average organic matter content of the brown soil at a depth of 0-20 cm was selected. It was determined that the organic matter content of the brown soil accounted for about 5.2% of the total mass of the brown soil. According to the weight percentage of the simulated coating, 5.2% humic acid was selected as the organic matter component of the brown soil.

[0041] The technical solution also relates to a method for preparing the simulated coating of freeze-thaw soil.

[0042] Example 9: Taking the chernozemite in Gongzhuling County, Changchun City, Jilin Province as an example, the preparation method of the simulated coating simulating the chernozemite in the region comprises the following steps: Under a 20°C environment, an acrylic monomer with good light transmittance is selected as a photocurable precursor, and according to the mass percentage of the simulated coating, 0.5% of the crosslinking agent is mixed with deionized water, and a magnetic stirrer is used to stir at a low speed for 10 minutes until it is completely dissolved, and the stirring speed is controlled between 300rpm-500rpm to prepare a primary solution; 0.01% of the photoinitiator is added to the primary solution, and the stirring speed is continued at a speed of 300rpm-500rpm for 20 minutes to make the photoinitiator dissolve completely. The initiator is fully dissolved and evenly distributed in the solution to obtain a secondary solution; the mineral components of the chernozem in the collection area are mainly montmorillonite, vermiculite and hydromica. According to the weight percentage of chernozem minerals, montmorillonite accounts for 20%, vermiculite accounts for 12%, and hydromica accounts for 5%. With reference to the mineral components and proportions of natural chernozem, montmorillonite, vermiculite and hydromica are mixed in a mass ratio of 4:2:1 and prepared into microparticles of 2μm-5μm in size. According to the weight percentage of the simulated coating, 15% of the prepared mixed mineral particles are slowly added to the secondary solution and stirred at a speed of 150rpm-300rpm for 3 hours. 0 minutes, so that the mineral particles are evenly suspended in the solution to form a soluble mineral mixture containing montmorillonite, vermiculite and hydromica. The stirring process of the above three stages should be carried out slowly and at a low speed while ensuring a uniformly mixed solution. Stirring too fast will easily cause bubbles in the solution. The bubbles will cause uneven distribution of the solidified materials and affect the stability of the materials. At the same time, the bubbles will also scatter light, affecting the curing efficiency and the transparency of the final coating. The prepared soluble mineral mixture is degassed using a vacuum degassing device, and the vacuum degree is controlled at -0.08Mpa to -0.09Mpa. The degassing time is 30 minutes to complete the degassing process. The bubbles in the solution are completely removed. The vacuum degassing in this step is also to achieve a good curing effect and ensure the light transmittance and performance stability of the cured material. The degassed mixed solution is filtered by a microporous membrane. Specifically, a polytetrafluoroethylene filter membrane with a pore size of 2-5 μm is used to intercept large particle impurities larger than 5 μm in the solution and retain small-sized mineral particles, which can ensure that the particles are evenly suspended in the solution to form a photocurable aqueous solution containing soluble minerals, that is, a simulated coating simulating the composition characteristics of chernozem is obtained. If not used immediately, the obtained photocurable aqueous solution needs to be stored in a light-proof container to prevent the photoinitiator from reacting prematurely.

[0043] When using the prepared soluble mineral photocurable aqueous solution, the solution is injected into a soil pore structure model with a pore structure distribution until it is evenly distributed, and then the soil pore structure model is placed under an ultraviolet light irradiation device for ultraviolet light irradiation for 10-12 minutes, so that the photocurable precursor is quickly cured. During this process, the soluble mineral particles are fixed on the pore structure surface inside the soil pore structure model. The ultraviolet light irradiation time needs to be strictly controlled to avoid excessive irradiation leading to material degradation or insufficient light leading to incomplete curing. After the photocuring is completed, the uncured solution residue in the soil pore structure model is rinsed with deionized water, and the soil pore structure model is placed in a clean environment for natural drying or quickly dried in a low-temperature oven. After drying, a coating layer simulating the mineral components on the surface of the frozen-thaw soil is formed on the pore structure surface in the soil pore structure model. The temperature during the preparation process needs to be maintained at 20-25°C to keep the physical and chemical properties of each component stable. The preparation should be carried out in a dark room or low-light environment to prevent external light sources from initiating photopolymerization reactions. The prepared aqueous solution containing soluble minerals should be used as soon as possible. Long-term storage can easily lead to degradation of the photoinitiator and affect the subsequent photocuring effect.

[0044] Example 10: Taking the black soil in Lishu County, Changchun City as an example, the preparation method of the simulated coating in this area comprises the following steps: in an environment of 20°C, an acrylic monomer with good light transmittance is selected as a photocurable precursor, and 3% of a crosslinking agent is mixed with deionized water according to the mass percentage of the simulated coating, and a magnetic stirrer is used to stir at a low speed for 15 minutes until it is completely dissolved, and the stirring speed is controlled between 300rpm-500rpm to prepare a primary solution; 0.05% of a photoinitiator is added to the primary solution, and the stirring speed is continued at a speed of 300rpm-500rpm for 20 minutes to make the photoinitiator fully dissolved and evenly distributed in the primary solution; The black soil in the collection area is mainly composed of montmorillonite and hydromica. According to the weight percentage of the collected black soil minerals, montmorillonite accounts for 26% and hydromica accounts for 25%. With reference to the mineral components and proportions of natural black soil, montmorillonite and hydromica are mixed in a mass ratio of 1:1 and prepared into microparticles of 2μm-5μm in size. According to the weight percentage of the simulated coating, 65% of the mixed mineral particles are slowly added to the secondary solution, and stirred at a speed of 150rpm-300rpm for 30 minutes to evenly suspend the mineral particles in the solution to form a soluble Mineral mixture, similarly, the stirring process of the first three stages needs to be carried out as slowly as possible while ensuring a uniformly mixed solution, so as to ensure the curing efficiency and the transparency of the final coating; 2% thickener is added to the prepared soluble mineral mixture, and stirred at a speed of 150-200rpm to uniformly mix the thickener and the soluble mineral mixture. As the stirring proceeds, the viscosity of the solution gradually increases, and the mixed solution eventually forms a viscous state; then the viscous mixture is degassed using a degassing device, specifically, a vacuum degassing device is used in combination with slow stirring to reduce the residence time of bubbles in the high-viscosity material system In particular, the vacuum degree is controlled at -0.08Mpa to -0.1Mpa, the stirring speed is 100rpm, and the degassing time is 40 minutes to completely remove the bubbles in the viscous mixture; the degassed mixture is pressure filtered, and the viscous material is squeezed through a filter with a diameter of 5μm under a pressure of 0.3Mpa to 0.5Mpa to remove the granular medium with a size greater than 5μm to form a light-cured viscous material containing soluble minerals, that is, a simulated coating simulating the characteristics of black soil components is obtained. If not used immediately, the obtained light-cured viscous material needs to be stored in a light-proof container to prevent the photoinitiator from reacting prematurely.

[0045] When using the prepared soluble mineral photocurable viscous material, the viscous material is dot-coated in the soil pore structure model, and the structure and position distribution of the multiple protrusions formed are determined according to the pore structure distribution of the simulated natural black soil, thereby simulating the pore structure distribution characteristics of the black soil. After the dot coating is completed, the soil pore structure model is irradiated under ultraviolet light for 12-15 minutes to solidify the multiple protrusions in the soil pore structure model. After the photocuring process, the uncured photocurable material residues in the soil pore structure model are rinsed with deionized water, and then the soil pore structure model is placed in a clean environment for natural drying or quickly dried in a low-temperature oven. Multiple protrusions simulating the distribution of black soil particles and mineral components are formed in the soil pore structure model, that is, a simulated coating of black soil is formed.

[0046] In the preparation method of the simulated coating described in the above-mentioned Example 9 and Example 10, organic components can be added simultaneously with the addition of mineral components to simulate the organic components in the soil environment and more realistically restore the multi-element complex environment of natural soil.

[0047] Example 11: Based on the method for preparing a simulated coating described in Example 9, a simulated coating of chernozem in Gongzhuling County, Changchun City, Jilin Province was prepared as an example to prepare a coating simulating soluble minerals and organic components of chernozem. Specifically, in the step of slowly adding 15% mixed mineral particles to the secondary solution, according to the organic matter content of the collected chernozem, the average organic matter content value of the soil depth of 0cm-18cm was selected. After measurement, the organic matter content of chernozem accounted for 3.3% of the total mass of chernozem. In particular, 3.3% humic acid (purchased from Shanghai Yuanye Biotechnology Co., Ltd.) was selected as the organic matter component in terms of the weight percentage of the simulated coating, and slowly added to the soluble mineral solution containing montmorillonite, vermiculite and hydromica, and stirred at a speed of 150rpm-300rpm for 30 minutes with the mixed mineral particles to prepare a mixed solution containing soluble minerals and organic components, and continued to perform subsequent degassing and filtration steps. Finally, a coating simulating the mineral and organic components on the surface of frozen-thawed chernozem was prepared.

[0048] Example 12: Based on the method for preparing a simulated coating described in Example 10, a simulated coating of black soil in Lishu County, Changchun City, Jilin Province was prepared as an example to prepare a coating of simulated soil soluble substances and organic components. Specifically, in the step of slowly adding 65% mixed mineral particles to the secondary solution, according to the collected black soil organic matter content, the average organic matter content value of the soil depth 0cm-20cm was selected. After measurement, the black soil organic matter content accounted for 6.3% of the black soil mass percentage. In particular, based on the weight percentage of the simulated coating, 6.3% humic acid (purchased from Shanghai Yuanye Biotechnology Co., Ltd.) was selected as the organic matter component, and slowly added to the soluble mineral solution, and stirred at a speed of 150rpm-300rpm for 40 minutes with the mixed mineral particles to prepare a mixed solution containing soluble minerals and organic components, and the subsequent thickener addition, degassing and filtration steps were continued. Finally, a coating simulating the mineral and organic components on the surface of frozen and thawed soil was prepared.

[0049] Similarly, a simulated coating was prepared for dark brown soil in Shuangyang District, Changchun City, Jilin Province. In the simulation experiment, 5.2% humic acid was selected as the organic matter component based on the weight percentage of the simulated coating.

[0050] In summary, the freeze-thaw soil simulation coating and its preparation method protected by the patent application of the present invention successfully simulate the mineral and organic components on the surface of soil particles through carefully designed and regulated process parameters and process flow, and significantly improve the complexity and simulation of soil pore structure simulation. By adding soluble minerals to simulate the mineral components of soil particles, the friction and adsorption properties of the surface of soil particles are enhanced, and organic matter is added to simulate the organic components in the soil environment, effectively restoring the porous medium structure and composition characteristics of natural soil. At the same time, by finely controlling the temperature, stirring conditions, degassing and filtration treatment during the preparation process, combined with the reasonable selection of cross-linking agents and photoinitiators and their dosage, the stability and mechanical strength of the simulated coating are ensured, and the material properties of no bubbles, high transparency and good light uniformity are achieved. These characteristics make the simulated coating have extremely high application value in the study of simulating the influence of soil particles on pollutant migration, and provide a professional and sophisticated experimental platform for in-depth exploration of the interaction between soil particles and pollutants and their migration and transformation mechanisms. This innovative achievement not only improves the precision and accuracy of soil simulation experiments, but also has important significance for understanding and predicting the behavior of pollutants in soil, providing a powerful experimental tool and theoretical basis for the field of soil environmental research.

Claims

1. A simulated coating for frozen-thawed soil, characterized in that: By weight percentage, the coating composition consists of: Crosslinking agent 0.5%-5%; Photoinitiator 0.01%-0.1%; Soluble minerals 10%-75%; The rest is deionized water, and the sum of each component is 100%. Among them, soluble minerals include montmorillonite and hydromica.

2. The simulated coating for frozen-thawed soil according to claim 1, characterized in that: The soluble minerals comprise 50% montmorillonite and 50% hydromica by weight.

3. The simulated coating for frozen-thawed soil according to claim 1, characterized in that: The soluble minerals include 20% montmorillonite, 12% vermiculite and 5% hydromica by weight percentage.

4. The simulated coating for frozen-thawed soil according to claim 1, characterized in that: The soluble minerals include 30%-50% hydromica, 10% vermiculite, 5% kaolinite and 3% montmorillonite in terms of weight percentage.

5. The simulated coating of frozen-thawed soil according to any one of claims 1 to 4, characterized in that: The crosslinking agent is ethylene glycol dimethacrylate, and the photoinitiator is benzophenone.

6. The simulated coating for frozen-thawed soil according to claim 5, characterized in that: The coating material is further added with 0.1%-2% thickener by weight, and the thickener is carboxymethyl cellulose.

7. The simulated coating for frozen-thawed soil according to claim 6, characterized in that: The simulated coating is further added with 3.3%-6.3% organic matter by weight, wherein the organic matter is humic acid.

8. The method for preparing a simulated coating according to any one of claims 1 to 7, characterized in that: The preparation method comprises: a) adding the crosslinking agent into deionized water at a ratio of 0.5% to 5% at 20-25°C, and stirring at a low speed until it is completely dissolved; b) adding 0.01%-0.1% photoinitiator to the mixed solution and stirring at a low speed for 15-20 minutes to fully dissolve the photoinitiator; c) slowly adding the soluble mineral into the mixed solution obtained in step b), stirring at a low speed for 25-35 minutes to uniformly suspend the mineral particles in the solution, and obtaining an aqueous solution containing the soluble mineral; d) Degassing the aqueous solution containing soluble minerals, controlling the vacuum degree at -0.08MPa to -0.1MPa, and the degassing time at 15-30 minutes; e) filtering the treated solution to remove particulate impurities larger than 5 μm, and storing the filtered solution in a light-proof container to prevent the photoinitiator from reacting prematurely.

9. The method for preparing a simulated coating according to claim 8, characterized in that: The speed of stirring the mixed solution in steps a), b) and c) is 150-500 rpm.

10. The method for preparing a simulated coating according to claim 9, characterized in that: 0.1%-2% thickener is added to the soluble mineral aqueous solution prepared in step c).